Analysis of Internal Controls, Individual Morality and Information Asymmetry Against Fraud Tendencies At PT. Ambassador Mayanksari in Surabaya - Dwi Dewianawati; Erry Setiawan; Darmayanti, Novi (Basic and Applied Accounting Research Journal, 2024)
This study aims to examine the influence of internal control, individual morality, and information asymmetry on the tendency of fraud in PT. Ambassador Mayanksari located in Surabaya. Fraud is a serious problem because it can harm a company both financially and reputationally. In this study, a quantitative approach was used with a survey method involving 57 respondents, who were employees of PT. Ambassador Mayanksari. The collected data was analyzed using multiple linear regression techniques to identify the relationship between independent and dependent variables. The findings show that all three variables—internal control, individual morality, and information asymmetry—together exert a significant influence on fraud propensity. Separately, internal control has been proven to have a positive influence on fraud tendencies. The same is true for individual morality and information asymmetry, both of which have a significant impact on the occurrence of fraud. This study suggests that the implementation of good internal control, the improvement of individual morality, and the reduction of information asymmetry can play an important role in reducing the potential for fraud in companies.